Formation of Highly Efficient Perovskite Solar Cells by Applying Li-Doped CuSCN Hole Conductor and Interface Treatment - In Seok Yang; You Jin Park; Yujin Hwang; Hoi Chang Yang; Jeongho Kim; Wan In Lee (Nanomaterials, 2022)
Li-doped CuSCN films of various compositions were applied as hole-transporting material (HTM) for mesoscopic perovskite solar cells (PSCs). Those films of ~60 nm thickness, spin-coated on the perovskite layer, exhibit significantly higher crystallinity and hole mobility compared with the pristine CuSCN films. Among them, 0.33% Li-doped CuSCN (Li0.33:CuSCN) shows the best performance as the HTM of mesoscopic PSC. Furthermore, by depositing a slight amount of PCPDTBT over the Li0.33:CuSCN layer, the VOC was increased to 1.075 V, resulting in an average PCE of 20.24% and 20.65% for the champion device. These PCE and VOC values are comparable to those of PSC using spiro-OMETAD (PCE: 20.61%, VOC: 1.089 V). Such a remarkable increase can be attributed to the penetration of the PCPDTBT polymer into the grain boundaries of the Li0.33:CuSCN film, and to the interface with the perovskite layer, leading to the removal of defects on the perovskite surface by paving the non-contacting parts, as well as to the tight interconnection of the Li0.33:CuSCN grains. The PSC device with Li0.33:CuSCN showed a high long-term stability similar to that with bare CuSCN, and the introduction of PCPDTBT onto the perovskite/Li0.33:CuSCN further improved device stability, exhibiting 94% of the initial PCE after 100 days.